Integrative Analysis of Hippocampus Gene Expression Profiles Identifies Network Alterations in Aging and Alzheimer’s Disease - Lanke, Vinay; Moolamalla, S. T. R.; Roy, Dipanjan; Vinod, P. K. (Frontiers in Aging Neuroscience, 2018)
Alzheimer’s disease (AD) is a neurodegenerative disorder contributing to rapid decline in cognitive function and ultimately dementia. Most cases of AD occur in elderly and later years. There is a growing need for understanding the relationship between ageing and AD to identify shared and unique hallmarks associated with the disease in a region and cell-type specific manner. Although genomic studies on AD have been performed extensively, the molecular mechanism of disease progression is still not clear. The major objective of our study is to obtain a higher-order network-level understanding of ageing and AD, and their relationship using the hippocampal gene expression profiles of young (20-50yrs), ageing (70-99yrs) and AD (70-99yrs). The hippocampus is vulnerable to damage at early stages of AD and altered neurogenesis in the hippocampus is linked to the onset of AD. We combined the weighted gene co-expression network and weighted protein-protein interaction network-level approaches to study the transition from young to ageing to AD. The network analysis revealed the organization of co-expression network into functional modules that are cell-type specific in ageing and AD. We found that modules associated with astrocytes, endothelial cells and microglial cells are upregulated and significantly correlate with both ageing and AD. The modules associated with neurons, mitochondria and endoplasmic reticulum are downregulated and significantly correlate with AD than ageing. The oligodendrocytes module does not show significant correlation with neither aging nor disease. Further, we identified ageing- and AD-specific interactions/subnetworks by integrating the gene expression with a human protein-protein interaction network. We found dysregulation of genes encoding protein kinases (FYN, SYK, SRC, PKC, MAPK1, Ephrin receptors) and transcription factors (FOS, STAT3, CEBPB, MYC, NFKβ and EGR1) in AD. Further, we found genes that encode proteins with neuroprotective function (14-3-3 proteins, PIN1, ATXN1, BDNF, VEGFA) to be part of the downregulated AD subnetwork. Our study highlights that simultaneously analyzing ageing and AD will help to understand the pre-clinical and clinical phase of AD and aid in developing the treatment strategies.